Fiber optical WDM multiplexers/demultiplexers with low bending losses - D. A. Ivanov (Российский технологический журнал, 2022)
Objectives. One of the topical tasks in the development of radio electronic systems for various purposes is a sharp increase in the volume and data transfer rate between the elements of the system. This problem is most successfully solved using fiber optic technology, which has no alternative to meet a number of indicators. The use of optical fibers (OF) as a physical medium made it possible to transfer large information flows over considerable distances. Increasing the capacity of communication systems is pushing manufacturers to develop new OF brands with improved optical and operational characteristics, which makes it possible to improve various optical components that use an OF as an active information transmission medium. The dual-channel single-mode wavelength division multiplexing (WDM) multiplexers/demultiplexers, which are one of spectral selective splitters types, are most widely used in fiber-optic communication systems. Among the advantages of WDM, it is worth to note the transmission of a large amount of information over one OF by the arrangement of channels at different wavelengths and the ability to transmit signals of several wavelengths simultaneously in both directions via one OF that do not interact with each other (duplex communication). During operation, WDM multiplexers can be subjected to various external influences that affect the operation and stability of the device parameters. Currently, there are no data on the effect of OF bending on the optical characteristics of WDM multiplexers. In this regard, it is important to study this dependence, which includes measuring the parameters of optical isolation and insertion loss. The purpose of the study is to work out the manufacturing technology and investigate the manufactured WDM multiplexers based on certain types of bend-resistant OF.Methods. For the formation of two-channel WDM multiplexers, the technology of fused biconical tapering was used, which makes it possible to achieve low insertion loss along with a high degree of channel isolation in the wide temperature range.Results. In the paper, the possibilities of manufacturing fiber multiplexers based on bend-resistant fiber Corning SMF-28 Ultra were discussed. The results of manufacturing and studying the experimental samples of WDM multiplexers optical characteristics were presented. It was established that the use of SMF-28 Ultra quartz fiber made it possible to significantly reduce the deviation of the channel optical isolation in the event of mechanical stresses in the multiplexers OF structure. Conclusions. The possibility of creating two-channel multiplexers with low bending losses and optical isolation up to 20–22 dB was experimentally shown. Possible mechanisms of the influence of the multiplexer fiber twisting on the optical isolation of channels were considered. The results obtained showed that when mechanical stresses in the fused structure of the multiplexer occur, the change in the optical isolation coefficient at two operating wavelengths does not exceed 1 dB.